2018
DOI: 10.1038/s41598-018-29208-w
|View full text |Cite
|
Sign up to set email alerts
|

Identification of ABCG2 as an Exporter of Uremic Toxin Indoxyl Sulfate in Mice and as a Crucial Factor Influencing CKD Progression

Abstract: Chronic kidney disease (CKD) patients accumulate uremic toxins in the body, potentially require dialysis, and can eventually develop cardiovascular disease. CKD incidence has increased worldwide, and preventing CKD progression is one of the most important goals in clinical treatment. In this study, we conducted a series of in vitro and in vivo experiments and employed a metabolomics approach to investigate CKD. Our results demonstrated that ATP-binding cassette transporter subfamily G member 2 (ABCG2) is a maj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
44
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 53 publications
(45 citation statements)
references
References 30 publications
1
44
0
Order By: Relevance
“…Kynurenic acid, which has a role in signaling in the central nervous system, is also an AHR ligand, as well as a ligand of the G protein-coupled receptor 35 (GPR35), which has also been associated with a number of diseases, including hypertension and heart failure (71,72). In this regard, it is worth noting that the metabolic derangements of uremia reflect aberrant functioning of normal interorgan and interorganismal remote sensing and signaling, involving, among other ADME genes, multispecific transporters, such as the OATs (31,(73)(74)(75)(76)(77).…”
Section: Discussionmentioning
confidence: 99%
“…Kynurenic acid, which has a role in signaling in the central nervous system, is also an AHR ligand, as well as a ligand of the G protein-coupled receptor 35 (GPR35), which has also been associated with a number of diseases, including hypertension and heart failure (71,72). In this regard, it is worth noting that the metabolic derangements of uremia reflect aberrant functioning of normal interorgan and interorganismal remote sensing and signaling, involving, among other ADME genes, multispecific transporters, such as the OATs (31,(73)(74)(75)(76)(77).…”
Section: Discussionmentioning
confidence: 99%
“…There are several possible mechanisms for the association between ABCG2 polymorphism and mortality. First, the ABCG2 transporter regulates not only uric acid, but also uremic toxins in chronic kidney disease (CKD) [12]. Our recent study showed that ABCG2-knockout CKD mice had higher mortality and decreased indoxyl sulfate excretion in the kidney and intestine [12].…”
Section: Discussionmentioning
confidence: 99%
“…First, the ABCG2 transporter regulates not only uric acid, but also uremic toxins in chronic kidney disease (CKD) [12]. Our recent study showed that ABCG2-knockout CKD mice had higher mortality and decreased indoxyl sulfate excretion in the kidney and intestine [12]. Indoxyl sulfate is a protein-bound uremic toxin resulting from bacterial metabolism of dietary tryptophan and is reported to be associated with mortality in CKD and dialysis patients [35−37].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations